The Impact of Parental Support and Interest Learning for the Result of Grade VIII SMP Negeri 12 Pematang Siantar Year 2023/2024 - Gerry Lineker Xaperius Simanjuntak (MultiTech Publisher, 2023)
This research aims to obtain knowledge regarding the influence of parental support and interest in learning on the learning achievement of Class VIII students at SMP Negeri 12 Pematang Siantar for the 2023/2024 academic year.This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 21. The population in this study was 277 people, and the sample used was 163 people. The sample collection technique used was Proportionate Stratified Random sampling. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2). The results of this study state that: 1) there is a positive influence of learning achievement on learning discipline. This result can be seen in the t test where the t value of parental support (5.657) > t table value (1.65437). 2) there is a positive influence of interest in learning on learning achievement. This result can be seen in the t test where the t value of interest in learning (5.689) > t table value (1.65437) which means this variable is significant. 3) parental support and interest in learning together influence learning achievement. This result can be seen in the F test where the Fcount value (1441.624) > Ftable value (3.05). The R Square coefficient of determination test was found to be 0.947, which means that 94.7% of the variables are the influence of parental support and interest in learning on the learning achievement of class VIII students at SMP Negeri 12 Pematang Siantar and 6.3% is the influence of other variables that were not examined in this research.